Cigarette Smoking Status Among Students of Primary School in Erzurum - Ünsal, A.; Sezgin, S. (My University, 2009)
Introduction: Tobacco use is one of the most important preventable health problems all over the world. The World Health Organisation (WHO) declared that smoking is the biggest health problem since over five million people die of it every year and it causes much harm. Most people begin to smoke in their early years and continue as an addiction. The aim of this descriptive cross-sectional study was to determine the smoking status of students at a primary school in the low socio-economic status region in Erzurum. Material and Method: The subject of the study was identified as 300 students from 5., 6., 7. and 8. grades in Maksut Efendi Primary School. All students were included in the study. However, 19.4% were not present in the school and 5% were not taken into consideration so the research was carried out with 230 students. Results: The ratios of boys and girls were 56.1% and 43.9%, respectively. Mean age was 12.9 years and 19.1% of students were smokers. The relation between gender and smoking behavior was statistically significant (p<0.001). There was statistically significant relation between parents' education level and smoking behavior (p<0.01, p<0.05). There was a statistically significant relation between father's and friends' smoking status and smoking behavior (p<0.01, p<0.05). National efforts to reduce smoking should be extended to students. Conclusion: Health professionals should play a predominant role in preventive measures, especially when considering the youth, and forewarn children and adolescents of the dangers of tobacco.
Erzurum İli İlköğretim Okulu Öğrencilerinin Sigara Kullanma Durumları
Keywords: Low Socio-Economic Status; Primary School Students; Smoking